Comparing the practices of USA skiing and snowboarding against a global model for integrated development of mass and high-performance sport - Smolianov, P.; Morrissette, J. N.; Boucher, C.; Dolmatova, T.; Schoen, C.; Dion, S. (Journal of Physical Education and Sport, 2022)
Problem Statement: The paper examines the current state of skiing and snowboarding in the USA against a model for developing high performance sport integrated with mass participation. The model stresses interconnections among the levels, such as macro-level policies used to impact healthy sport behaviors through regulations of advertising and marketing, school provisions, retail offerings, and taxes and levies, which directly and indirectly influence sport development at meso- and micro-levels. When the performance and health of athletes and masses of general population are advanced in integration, this ultimately helps reach goals of many supporting agencies and contribute to macro-level socio-economic success. Approach: We developed a questionnaire to examine the following elements of the model: talent development; advanced athlete support; training centers; competitions; intellectual services; partnerships with supporting agencies; balanced and integrated funding and structures of mass and elite sport. Survey questions were validated by 12 international experts including executives from sport governing bodies, coaches, academicians, and administrators. To determine the areas for improvement, 102 coaches completed the questionnaire. Possible advancements were further identified through semi-structured discussions with 10 skiing and snowboarding administrators. Purpose: This study investigated the integrated sport development from recreation to high performance at macro, meso, and micro levels of support and policy on the example of the United States Ski and Snowboard Association. Macro level elements refer in this study to socio-economic, cultural, legislative, and organizational support for a national sport system by the whole society. The meso level includes infrastructures, personnel, and services enabling delivery of sport policy. The micro level consists of operations, processes, and methodologies for development of individual athletes. Results and Conclusions: The sport system components overlap at different levels, therefore they create opportunities for a holistic system of sport development where high performance programs are integrated with mass participation provisions. Results suggest possible enhancements at macro level (e.g., new partnerships and incentives for greater support of mass participation), meso level (e.g., additional sources and models for better coach education and facilities), and micro level (e.g., advanced lifelong guidelines for excellence of everyone) on the example of USSA. It is important to use this holistic approach in further research on the integrated development of mass and high-performance sport.